2019
DOI: 10.1101/746974
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic screens reveal a central role for heme biosynthesis in artemisinin susceptibility

Abstract: Artemisinins have revolutionized the treatment of Plasmodium falciparum malaria, however, resistance threatens to undermine global control efforts. To explore artemisinin resistance in apicomplexan parasites broadly, we used genome-scale CRISPR screens recently developed for Toxoplasma gondii to discover sensitizing and desensitizing mutations. Using a sublethal concentration of dihydroartemisinin (DHA), we uncovered the putative porphyrin transporter Tmem14c whose disruption increases DHA susceptibility. Scre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 111 publications
(130 reference statements)
0
18
0
Order By: Relevance
“…We consider TGME49_290840 to be the more likely mitochondrial DegP2 ortholog based on the presence of a DegP-htrA superfamily motif and detection in the mitochondrial proteome (49). Moreover, a recent study in T. gondii reported that this gene is localized to the mitochondrion and it can be deleted without major loss of fitness (50). The T. gondii DegP2 ortholog was mutated in a different position in each of the F4 and B2 lines, although both nonconservative mutations resided in the PDZ2 domain (DegP2-F4-E821Q and DegP2-B2-G806E) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We consider TGME49_290840 to be the more likely mitochondrial DegP2 ortholog based on the presence of a DegP-htrA superfamily motif and detection in the mitochondrial proteome (49). Moreover, a recent study in T. gondii reported that this gene is localized to the mitochondrion and it can be deleted without major loss of fitness (50). The T. gondii DegP2 ortholog was mutated in a different position in each of the F4 and B2 lines, although both nonconservative mutations resided in the PDZ2 domain (DegP2-F4-E821Q and DegP2-B2-G806E) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Generation of ALA from succinyl‐CoA and glycine is catalyzed by ALAS in the mitochondrion, as in animals and yeast. In T. gondii , the succinyl‐CoA is expected to be derived from the TCA cycle, as inhibiting the pathway resulted in a decrease in heme production [16], while glycine can be derived from serine in the cytoplasm or directly salvaged from the host and transported to the mitochondria [110]. The subsequent four steps occur in the apicoplast, a relict plastid organelle derived from secondary endosymbiosis of a red alga [108,111,112].…”
Section: Heme Synthesis Enzymes In Apicomplexa: Conservation Localizmentioning
confidence: 99%
“…In model organisms, heme synthesis is highly regulated at multiple levels based on the state of the cell and availability of precursors [103,131,132]; for example, ALAS activity is inhibited by binding to heme, allowing negative regulation of heme production [133]. In extracellular parasites, addition of ALA leads to an excess of PPIX but no or only a modest increase in heme, indicating that ALA stimulates PPIX synthesis in T. gondii , while FECH is rate limiting for its conversion to heme [16]. The same effect of ALA supplementation is well known for mammalian cells and has been exploited for photodynamic therapy of cancer cells, which become light sensitive upon PPIX accumulation [134–136].…”
Section: Regulation Of Heme Synthesis In Apicomplexamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that enhancing heme synthesis, by providing excess heme precursors, increases the sensitivity of Plasmodium to artemisinin. Conversely, the reduction of heme synthesis by genetic means or through pharmacological inhibition decreases sensitivity of both T. gondii and P. falciparum to artemisinin (113,114).…”
Section: Hemementioning
confidence: 99%